Cost Analysis of Drug-related Problems in Saudi Arabia: Patients’ and Healthcare Providers’ Perspective - Alomi, Yousef Ahmed; Al-Shaibani, Awatif Saad; Ghadeer, Alfaisal; Alasmi, Njood Mohmmed (Journal of Pharmacy Practice and Community Medicine)
Purpose: To explore the cost analysis of drug-related problems in Saudi Arabia from patient and healthcare provider’s perceptive. Methods: It is a 4-months cross-sectional survey of drug-related problem information in Saudi Arabia. The survey consisted of two-part demographic information, and second part consisted of thirteen questions focusing on general knowledge of drug-related problems, their occurrence, and costs. The questions divided into three domains. It included domain 1: Primary or essential information about knowledge and perception of drug-related problems, domain 2: The cost analysis of drug-related problems, domain 3: Clinical outcome of drug-related problems. The questions about the cost of drug-related problems, health insurance coverage and the economic outcome of those issues including pharmacy visit, ambulatory care clinic visit, an emergency visit, hospital admission, critical care admission, drug-induced death. The American Society of Health-System Pharmacist definitions of drug-related problems used. The survey distributed through social media by using what’s App to almost two thousand public and healthcare professionals overall Kingdom of Saudi Arabia. It analyzed domain two the cost analysis of drug-related problems through survey monkey system. Results: The total responders were one hundred and one. Of those 155 (77.9%) were patients while 44 (22.1%) were healthcare professionals. The gender distribution was female 180 (89.6%), and the male was 21 (10.4%). It is statistically non-significant (p< 0.5) in the in the female and males between Patient and healthcare professionals. The most age was (18-44) represented the eighty-eight percent of responders. The highest estimated cost of patients suffered from drug-related problems was adverse drug reactions (3,525.42 USD) and drug non-compliance (2,594.26 USD) followed by indications without medication (2483.83 USD). The most frequencies of type drug-related problems per patients were drug noncompliance (4.15 fold) and medication without indications 3.75 fold) followed by drug interaction (3.7 fold) and indication without medications (3.52 fold). The highest estimated average cost of drug-related problems for patients was adverse drug reaction (1733.33 USD) and medication errors (762.67 USD) followed by drug noncompliance (624.44 USD) and drug interaction (593.33 USD). The total estimated average cost of related problems annually was (122 Billion USD) within range (60 Billion USD) and (184 Billion USD) in Saudi Arabia. It included the cost of non-compliance was (36 Billion USD), the cost of adverse drug reaction was (31 Billion USD), and the cost of indication without medications problem was (24 Billion USD). Conclusion: The drug-related problems were a very high-cost burden on health care system in Saudi Arabia. Targeting to improve role of pharmacist and prevent drug-related misadventures is highly recommended through Saudi Health Care Vision 2030.
Keywords: Cost analysis; Drug-related problems; Patients; Healthcare providers; Perspective; Saudi Arabia